UPAYA MENINGKATKAN HASIL BELAJAR SISWA KELAS V PADA TEMA MAKAN SEHAT DENGAN METODE QUIZ TEAM DI SEKOLAH SDN 066667 MEDAN DENAI - Winda Shafira Putri (PGSD UMN Al-Washliyah, 2022)
This study aims to determine the improvement of student learning outcomes in science subjects with the theme of healthy eating with the Quis Team method. This research was conducted in class V SD Negeri 066667 Medan Denai. This research is a classroom action research (Classroom Action Research). The subjects in this study were fifth grade students of SD Negeri 066667 Medan Denai, totaling 15 people. The instruments and data collection techniques used in this study were observation and tests. From the observations, it is known that only 5 students scored above the Minimum Completeness Criteria (KKM) and 10 students below the KKM. The percentage of student learning outcomes only reached 33%. After taking action in cycle I, there was an increase in student learning outcomes. The percentage of student learning outcomes in the first cycle of the first meeting, which is 46%, the percentage of student learning outcomes in the first cycle of the second meeting, is 60% and the percentage of student learning outcomes in the first cycle of the third meeting, which is 66%. There was an increase in student learning outcomes by 27% in the first cycle, from 33% at the time of observation to 60% at the end of the first cycle. The percentage of student learning outcomes in the second cycle of the first meeting was 73%, the percentage of student learning outcomes in the second cycle of the second meeting , which is 86% and the percentage of student learning outcomes in the second cycle of the third meeting, which is 93%. There was an increase in student learning outcomes by 47% in the second cycle, from 33% at the time of observation to 80% at the end of the second cycle. Thus, it can be concluded that the use of the quiz team method can improve student learning outcomes on the theme of healthy eating in class V SD Negeri 066667 Medan Denai.